Help-Seeking for Severe Intimate Partner Violence Among Sexual and Gender Minority Adolescents and Young Adults Assigned Female at birth: A Latent Class Analysis. Issue 9 (May 2023) - Scheer, Jillian R.; Lawlace, Margaret; Cascalheira, Cory J.; Newcomb, Michael E.; Whitton, Sarah W.
Sexual and gender minority adolescents and young adults assigned female at birth (SGM-AFAB) report high rates of intimate partner violence (IPV) victimization. Despite adverse health outcomes of IPV, many survivors, particularly SGM-AFAB, do not seek help. This study (1) examined the proportion of SGM-AFAB who reported severe IPV victimization who sought help; (2) elucidated patterns of help-seeking facilitators and barriers; and (3) identified associations between sociodemographic characteristics, IPV victimization types, and minority stressors and latent classes of help-seeking facilitators and barriers. Participants included 193 SGM-AFAB (Mage = 20.6, SD = 3.4; 65.8% non-monosexual; 73.1% cisgender; 72.5% racial/ethnic minority; 16.6% annual household income 20, 000 or less). Most participants who experienced severe IPV did not seek help (62.2%). Having a person or provider who was aware of the participant's abusive relationship was the most common reason for seeking help (50; 68.5%). Minimizing IPV was the most common reason for not seeking help (103; 87.3%). Fewer than 5% of SGM-AFAB who experienced severe IPV and who did not seek help reported SGM-specific help-seeking barriers, including not wanting to contribute to negative perceptions of the LGBTQ community, not disclosing their SGM status, and perceiving a lack of tailored services. Help-seeking facilitators and barriers varied by sociodemographic characteristics. Three classes of help-seeking facilitators and two classes of help-seeking barriers emerged. SGM-AFAB subgroups based on sexual and gender identity, recent coercive control, and identity as IPV victims differed in latent classes. This study's findings confirm SGM-AFAB IPV survivors' low likelihood of seeking help. Our results also underscore the importance of continuing to bolster SGM-AFAB survivors' access to trauma-informed, culturally sensitive, and affirming support. Further, multilevel prevention and intervention efforts are needed to reduce minimization of abuse and anticipatory judgment and blame among SGM-AFAB who hold multiple marginalized identities, experience coercive control, and identify as IPV victims.